Stress, depression and obesity among adolescents: a narrative review - Tajik, E.; Abd. Latiff, Latifah; Javadi, M.; Mohammadzadeh, M. (2015)
Adolescents try to eat as a way to stress relief, while they suffer from overweight and obesity and feel depressed later. This is a review and analysis of the results of published research literature since 1980 on the relationship of obesity with stress and depression among adolescents. The current review tries to evaluate and describe the effect of stress on obesity and subsequently on depression among adolescents. The literature reveals obvious differences in various emotional problems for boys and girls. However, some studies focused on stress and obesity among adolescents, some others reported depression among obese adolescents. Descriptive design was used for quantitative studies as well as using theories which were used for qualitative studies. Interview and questionnaires were used for data collection. Studies revealed that stress results in overweight and obesity among adolescents through decreasing physical activity and increasing food intake. Consequently, obesity among adolescents as a result of negative body image and concept of proper appearance can cause depression. On the other hand, gender, age and ethnicity affect stress and depression as well as obesity during adolescence.